2022
DOI: 10.3390/molecules27217167
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Astaxanthin as a Nutraceutical in Health and Age-Related Conditions

Abstract: The current review provides an up-to-date analysis of scientific data on astaxanthin (ASX) sources and experimental studies on its health benefits as a potent antioxidant in the aging process. ASX is a liposoluble carotenoid nutrient and reddish-orange pigment, naturally synthesized by numerous microalgae, yeasts, and bacteria as secondary metabolites. Provides a reddish hue to redfish and shellfish flesh that feed on ASX-producing microorganisms. The microalga Haematococcus pluvialis is the most important sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…Carotenoids are a diverse group of lipid-soluble pigments produced by plants and microorganisms, known for their benefits as vitamin precursors and antioxidants. Astaxanthin, a ketocarotenoid, is recognized as one of the most powerful natural antioxidants among carotenoids [202]. Astaxanthin is currently primarily produced industrially from the microalgae Haematococcus pluvialis, with the crucial enzyme involved in its biosynthesis being β-carotene ketolase (BKT) [203].…”
Section: High-value Bioproductsmentioning
confidence: 99%
“…Carotenoids are a diverse group of lipid-soluble pigments produced by plants and microorganisms, known for their benefits as vitamin precursors and antioxidants. Astaxanthin, a ketocarotenoid, is recognized as one of the most powerful natural antioxidants among carotenoids [202]. Astaxanthin is currently primarily produced industrially from the microalgae Haematococcus pluvialis, with the crucial enzyme involved in its biosynthesis being β-carotene ketolase (BKT) [203].…”
Section: High-value Bioproductsmentioning
confidence: 99%
“…Astaxanthin ( Figure 13 ) is another fat-soluble xanthophyll carotenoid with a red pigmentation, which is found in various microorganisms and marine animals and algae [ 292 , 293 ] such as Haematococcus pluvialis , a green microalga, which accumulates high astaxanthin amounts under stress conditions of high salinity, nitrogen deficiency, high temperature, and light [ 294 , 295 , 296 ]. In a few years, it has been approved to be used as a food colorant in animal and fish feed such as salmon, trout, and shrimp [ 292 , 297 ] and used as a nutritional supplement and has been rapidly growing in foods, feeds, nutraceuticals, and pharmaceuticals [ 298 , 299 ].…”
Section: Natural Antioxidants and Their Benefitsmentioning
confidence: 99%
“…Carotenoid lycopene, which accumulates significantly in ripe tomatoes, demonstrated protection against diabetes and obesity [ 113 ]. Bjørklund et al [ 114 ] revealed the ability of the other carotenoid astaxanthin, synthesized by numerous microalgae, yeasts, and bacteria, to manage the overweight outcome. Radice et al [ 115 ] found that supplementation of the experimental animals with astaxanthin had positive effects on a variety of symptoms associated with obesity through the hypoglycemic and lipid-lowering capacity, as well as mitigating the immune system.…”
Section: Novel Drugs In Obesity Treatmentmentioning
confidence: 99%